Perioperative anesthesia management for elderly patients with permanent pacemakers undergoing retropubic prostatectomy in Ethiopia East Africa: a case report and review of the literature - Eniyew Assimie Alemu; Biruk Adie Admass; Demelash Gedefaye Anteneh; Desyibelew Chanie Mekonnen; Molla Amsalu Tadesse (Journal of Medical Case Reports)
Abstract Backround Perioperative anesthesia management for elderly patients with permanent pacemakers is complex, particularly in low-income countries. Preoperative pacemaker assessment and adjusting to asynchronous mode are crucial to avoid adverse events. Positioning electrocautery below the umbilicus and planning anesthesia to minimize pacemaker interference can reduce perioperative complications. This case involves an elderly male undergoing retropubic prostatectomy with a permanent pacemaker in dual-chamber, rate-modulated mode, without changing it to asynchronous mode, highlighting a rare anesthetic challenge in such settings. Clinical presentation A 78-year-old male from the Amhara region, Ethiopia, with a permanent pacemaker for complete heart block was scheduled for retropubic prostatectomy. Preoperative assessments by the anesthetist and cardiologist recommended reprogramming the pacemaker to asynchronous mode to reduce risks related to its dual-chamber, rate-modulated mode setting. However, the patient could not afford reprogramming and opted to proceed with the existing perioperative plan. Informed consent was obtained, and case report publication permission was obtained after operation. The patient received combined epidural–spinal anesthesia with 2.50 ml of 0.5% isobaric bupivacaine and 50 µg fentanyl at the L3–L4 interspace. Standard American Society of Anesthesiology monitoring was applied, with a focus on cardiac stability. The patient remained stable with minimal vital sign fluctuations and maintained adequate blood pressure using isotonic saline. Postoperatively, the patient was transferred to the postanesthesia care unit, receiving analgesia after 4 hours and an epidural top-up. After 6 hours, he was transferred to the ward in stable condition. Epidural analgesia was continued for 72 hours, and the patient was discharged on the 88th postoperative hour in stable condition. Conclusion Elderly patients with permanent pacemakers undergoing noncardiac surgery require thorough preoperative assessment and careful anesthesia management. In this case, financial constraints led to the decision not to reprogram the pacemaker, necessitating meticulous planning and monitoring during surgery. Using combined epidural–spinal anesthesia can enhance safety and outcomes, especially in low-resource settings where alternative anesthetic and resuscitative options may be limited.